Kelayakan Media Booklet Sawi Dayak (Elephantopus mollis Kunth) pada Pembelajaran Biologi Mahasiswa - Ruqiah Ganda Putri Panjaitan*; Andi Besse Tenriawaru (Jurnal Pendidikan Sains Indonesia, 2022)
Learning media can be arranged based on the results of literature studies from research on an object. This study aims to determine the feasibility of learning media booklet sawi dayak (Elephantopus mollis Kunth). The stages in this research include the stage of collecting information through a literature study on the efficacy of the mustard mustard plant, the booklet preparation stage, the booklet validation stage, and the booklet revision stage in accordance with the suggestions from the validators. Aspects that are assessed in the feasibility test are aspects of format, content, and language. The results of the validation were then analyzed using Gregory's calculations. The results of data analysis show that the aspects of format, content, and language each get a value of 1.00 and the average of these three aspects is 1.00 with a very high validity category. It is concluded that this booklet media can be used as a learning medium